Cervical esophageal duplication cyst in a pediatric patient: A case report - Souha Laarif; Rabiaa Ben Abdallah; Cyrine Saadi; Fatma Trabelsi; Aida Daïb; Youssef Hellal (Journal of Pediatric Surgery Case Reports)
Introduction: Esophageal duplications are rare congenital anomalies with an incidence of 1 case per 100,000 live births. They most commonly present in a cystic form, and involvement of the cervical esophagus is particularly rare. Case presentation: A 2-year-old girl was referred to us due to a progressively enlarging right cervical mass and dysphagia. She had no past medical or surgical history. On physical exam we found a 4-cm nodule in the right cervical region. The nodule was soft, mobile, non-tender and not inflamed. A cervicothoracic magnetic resonance imaging (MRI) showed a 4× 4 × 5 cm unilocular paratracheal cystic mass with airway displacement and moderate tracheal stenosis. The patient was taken to the operating room for a cervical exploration through a right cervicotomy. We found a cystic mass surrounded by a thin smooth muscle layer firmly attached to the esophageal wall but not communicated with the esophageal lumen. The mass was detached off all the surrounding structures and resected completely. The histological examination confirmed the diagnosis of a cervical esophageal duplication cyst. Postoperative, a contrast study showed regular peristalsis, no extravasation and no stenosis. At three years of follow-up, she has no signs of recurrence. Conclusion: Although rare, cervical esophageal duplications should be considered in the differential diagnosis of children who present with a palpable cervical mass. Complete surgical resection is the definitive treatment.